Optimization scheduling of virtual power plant with carbon capture and waste incineration considering P2G coordination. (November 2022) - Zhang, Zongnan; Du, Jun; Zhu, Kongge; Guo, Jing; Li, Menghan; Xu, Tao
Abstract: In order to promote multi-energy complementation and low carbonization, an optimal scheduling model of virtual power plant (VPP) with carbon capture and waste incineration considering power-to-gas coordination is proposed. By introducing the collaborative utilization framework with a carbon capture plant-power to gas (P2G)-gas unit system, the CO2 in the carbon capture can be used as the raw material of P2G, which produces natural gas to be supplied to the gas unit. In addition, the power consumption of the carbon capture and the flue gas treatment can be transferred through joint dispatching to smooth the fluctuation of renewable energy output, so that the wind power and photovoltaic can be indirectly dispatchable and flexibly utilized. In view of the high dimensional nonlinearity of the proposed optimization model and the difficulty in solving it, a new Gaussian compound differential evolution algorithm is designed to solve the model. The simulation results show that the proposed model and method can provide peak load shifting capacity and improve renewable energy consumption, effectively reducing the cost and carbon emission of VPP.